Association Between SIRT1, Cytokines, and Metabolic Syndrome in Schizophrenia Patients With Olanzapine or Clozapine Monotherapy - Fang, Xinyu; Yu, Lingfang; Wang, Dandan; Chen, Yan; Wang, Yewei; Wu, Zenan; Liu, Ruimei; Ren, Juanjuan; Tang, Wei; Zhang, Chen (Frontiers in Psychiatry, 2020)
Objective: Previous studies consistently showed the interaction between Sirtuin 1 (SIRT1) and immune inflammation is significantly related to metabolic abnormalities, but their role in the pathogenesis of metabolic syndrome caused by second-generation antipsychotics (SGAs) in schizophrenia patients largely remains unknown. Hence, the present study aimed to fill this gap. Methods: A total of 54 schizophrenia patients with olanzapine or clozapine monotherapy [metabolic syndrome (MetS)/non-MetS patients, 27/27] and 67 healthy subjects were recruited in the present study. The Positive and Negative Syndrome Scale was used, and the plasma levels of SIRT1, interleukin 6 (IL-6), IL-8, IL-10, and tumor necrosis factor α (TNF-α) were measured. Results: The results showed that schizophrenia patients treated with olanzapine or clozapine (both MetS and non-MetS groups) had significantly higher plasma levels of IL-6, IL-10, and TNF-α compared to normal controls (all P < 0.05). Moreover, the MetS patients exhibited markedly lower plasma levels of SIRT1 and higher plasma levels of IL-6 than non-MetS patients and normal controls (all P < 0.05). However, there were no significant differences in IL-8 levels between groups. Our correlation analysis showed that SIRT1 was significantly correlated with diastolic blood pressure, triglyceride, and high-density lipoprotein cholesterol in schizophrenia patients. The stepwise logistic regression analysis further identified the IL-6 × SIRT1 (β = −0.463, t = 10.040, P = 0.002) as the influencing factor for the MetS in the patients. Conclusion: Our preliminary findings suggest that SIRT1 interacted with inflammatory cytokines associated with MetS in schizophrenia patients treated with SGA monotherapy.